2003
DOI: 10.1046/j.1470-6431.2003.00288.x
|View full text |Cite
|
Sign up to set email alerts
|

The importance of origin as a quality attribute for beef: results from a Scottish consumer survey

Abstract: Perception of country of origin and purchasing habits for beef were examined for urban and rural Scottish consumers. Origin was identified as being as important as intrinsic quality cues of colour and leanness, with rural consumers giving more weight to origin than urban ones. Most consumers interpreted ‘Scotch Beef’ and ‘British Meat’ label logos as evidence that the beef animals were ‘born, raised and slaughtered in Scotland or Britain’ respectively. The logos were taken as indicators of quality and safety. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
39
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 10 publications
5
39
0
2
Order By: Relevance
“…Credence cues cannot be verified readily by the consumer upon consumption (Davidson et al 2003). Credence cues include nutrition, the presence of genetically modified food, the adoption of sustainable agricultural production systems, considerations for animal welfare, fair trade and the prohibition of forced and child labor (Steenkamp 1990).…”
Section: Credence Cuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Credence cues cannot be verified readily by the consumer upon consumption (Davidson et al 2003). Credence cues include nutrition, the presence of genetically modified food, the adoption of sustainable agricultural production systems, considerations for animal welfare, fair trade and the prohibition of forced and child labor (Steenkamp 1990).…”
Section: Credence Cuesmentioning
confidence: 99%
“…According to Davidson et al (2003), consumers usually rely on actors within the supply chain to provide honest and meaningful information, as evidenced by the presence of labels and independent third party, quality assurance certificates.…”
Section: Credence Cuesmentioning
confidence: 99%
“…Consumers believe that free-range access is important for broiler chicken welfare (De Jonge and Van Trijp, 2013;Vanhonacker et al, 2016). Concerns about animal welfare is one driver for consumers to buy particular products (Fearne and Lavelle, 1996;Hill and Lynchehaun, 2002;Davidson et al, 2003;Vanhonacker et al, 2010). But welfare is not the only driver: a Belgian study showed that when buying chicken meat, product attributes such as healthiness, quality, consistent.…”
Section: Introductionmentioning
confidence: 99%
“…However, when consumers face choices between more familiar domestic products and unfamiliar imported products, domestic products are more likely to be chosen, as the lack of knowledge regarding the quality of imported products could induce uncertainty (Marette, Clemens, & Babcock, 2008). In addition, studies have showed that consumers invoke food-safety perceptions from COOL (Becker, 2000;Davidson, Schröder, & Bower, 2003;Schupp & Gillespie, 2001). Given that food sold in retail markets was not previously required to be labeled with place of origin information, a natural question arises: are consumers familiar enough with imported food, such that their perceptions about food safety of imported food correctly reflects the reality about the safety of these products, and if not, how do these subjective perceptions influence consumers' preferences?…”
Section: Introductionmentioning
confidence: 99%